Deletion in the EVC2 gene causes chondrodysplastic dwarfism in Tyrolean Grey cattle. - Leonardo Murgiano (Public Library of Science (PLoS), 2014)
During the summer of 2013 seven Italian Tyrolean Grey calves were born with abnormally short limbs. Detailed clinical and pathological examination revealed similarities to chondrodysplastic dwarfism. Pedigree analysis showed a common founder, assuming autosomal monogenic recessive transmission of the defective allele. A positional cloning approach combining genome wide association and homozygosity mapping identified a single 1.6 Mb genomic region on BTA 6 that was associated with the disease. Whole genome re-sequencing of an affected calf revealed a single candidate causal mutation in the Ellis van Creveld syndrome 2 (EVC2) gene. This gene is known to be associated with chondrodysplastic dwarfism in Japanese Brown cattle, and dwarfism, abnormal nails and teeth, and dysostosis in humans with Ellis-van Creveld syndrome. Sanger sequencing confirmed the presence of a 2 bp deletion in exon 19 (c.2993_2994ACdel) that led to a premature stop codon in the coding sequence of bovine EVC2, and was concordant with the recessive pattern of inheritance in affected and carrier animals. This loss of function mutation confirms the important role of EVC2 in bone development. Genetic testing can now be used to eliminate this form of chondrodysplastic dwarfism from Tyrolean Grey cattle.